Foreign Direct Investment, Government Capacity, and Sustainable Development Goals in Indonesia: Evidence from a Dynamic Causality Approach - Dorothea Bening Larasati (Universitas Airlangga, 2026)
Background: Indonesia has begun to view Foreign Direct Investment (FDI) as a potential source of funding for development. However, the relationship among FDI, government capacity, and progress toward the Sustainable Development Goals (SDGs) across the economic, social, environmental, and institutional dimensions remains underexplored empirically. Objective: This study aims to analyze the relationships among government fiscal capacity, the achievement of the Sustainable Development Goals (SDGs), and foreign direct investment (FDI) in Indonesia, and to examine whether FDI influences sustainable development. In this study, government capacity is defined as the state's fiscal ability to finance development, measured by the allocation of public spending to the health and education sectors. Method: This study uses annual time-series data from 2000 to 2024 and analyzes it using the Vector Autoregression (VAR) approach and the Toda-Yamamoto causality test. Given that the SDGs were officially introduced in 2015, SDG indicators for the period prior to 2015 were constructed using a backdated data approach based on Millennium Development Goals (MDGs) indicators as well as statistical data that has been harmonized in the Sustainable Development Report, thereby ensuring the consistency of the time series and avoiding anachronistic bias. Stationarity tests were conducted using the Augmented Dickey-Fuller test, while causal relationships were tested using the Modified Wald Test. Results: The research findings indicate that FDI has no direct causal effect on most SDG pillars, in either the short or long term. The impact of FDI is only evident in the economic pillar in the long term, while no significant relationship was found in the social and environmental pillars. Conversely, government variables play a more dominant role in influencing sustainable development outcomes. Conclusion: These findings indicate that FDI cannot automatically drive the achievement of sustainable development without adequate government capacity. Therefore, fiscal and institutional frameworks must be strengthened to channel foreign investment more effectively in support of the SDGs. Keywords: FDI, Government Capacity; Indonesia; Sustainable Development Goals; Toda-Yamamoto Causality